Analisis Hukum Islam Terhadap Praktik Investasi Emas Online Melalui Platform Pegadaian Digital - Wandira Anzani; Shabilla Aisyah; Dwi Anggriani; Muhammad Abdi; Siregar, Fahmi Apriyansyah; Ogin Syahputra Sinaga; Ramadhan Saleh Lubis (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
The rapid development of financial technology (fintech) has driven innovation in the world of investment, one of which is through digital platforms for gold investment. Pegadaian Digital, as an online gold investment service, offers ease of access and flexibility for the public, but raises issues of Islamic law regarding the suitability of contracts, ownership, and transaction mechanisms in a non-physical system. This study aims to analyze the compliance of online gold investment practices at Pegadaian Digital with Islamic legal principles. The research employs a qualitative method with a normative-legal and conceptual approach, and data is obtained through literature review, including fiqh literature, DSN-MUI fatwas, and official documents from Pegadaian. The results of the study indicate that digital gold investment through Pegadaian Syariah uses a combination of wakālah, ijarah, bai’, and qardh contracts, which are considered valid under Islamic law, provided they meet the conditions and requirements of the contract and are free from elements of riba and gharar. The delivery mechanism in the digital system is deemed valid based on the concept of qabḍ hukmī (legal delivery), and does not contradict sharia if the transaction object, price, and rights and obligations of the parties are explained transparently. The conclusion of this study states that online gold investment practices through Pegadaian Digital can be considered in line with Sharia principles, provided they remain under continuous supervision to align with the objectives of Sharia (maqāṣid al-syarī‘ah) in contemporary muamalah practices.